Methodological approaches for perfection of social accompaniment of the HIV- infected people using injection drugs in Almaty (The Journal of Psychology and Sociology, 2017)
There were designed the main elements of the components of social support models among HIV-infected patients and their sexual partners, who represented a multi-level process directed to ensure people living with HIV / AIDS, his friends and relatives to have timely access to medical and psychological care and proper coordination of these services. Essentially formulated approaches and principles for creating social support models are represented complex measures to improve the access of HIV-positive IDUsrepresent and their sexual partners to the health and psychosocial support services. The model includes: the components of medical and social support, standards, step by step procedures. There were provided evaluation, correction plan for the provision of services and care.The study attempted to form a basic methodological principles of the model of social support to HIV-positive people who inject drugs and their sexual partners in a city of Almaty. They are an important link in providing this category of the popu-lation’s access to timely services and provision of the necessary resources and the implementation of a broader sector of the problems associated with HIV infection, thus achieving an overall improvement of quality of life of people living with HIV.
Keywords: HIV infection; social support; model; people; injecting drug users (IDUs).